The Effectiveness of Using a Case Study-Based Module on Learning Outcomes in Segmenting, Targeting and Positioning Strategies - Istianah Istianah; Harti Harti; Norida Canda Sakti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to test the effectiveness of case study-based modules on learning outcomes in segmenting, targeting, and positioning in vocational high schools. The type of research used is Pre-Experimental. In this study, the One Group Pretest-Posttest. In this research, the treatment given is using case study-based modules on segmenting, targeting, and positioning. This research was conducted at SMK Negeri 1 Bangkalan. Research subjects are students of class X Online Business and Marketing, totaling 20 students. Before treatment, the students were given a pretest. After the treatment, the students were given a posttest of 20 questions. Improving learning outcomes was analyzed using the T-Test and N-Gain formulas. The T-test is used to calculate whether the increase in learning outcomes is significant or not. In contrast, N-Gain is used to calculate the increase in learning outcomes. The improvement of learning outcomes based on the N-gain analysis shows that the learning outcomes are categorized as moderate, thus showing that pretest and post-test there are differences based on the results of the T-Test (Paired Sample T-test).